Bilateral trade with loss-averse agents - Jean-Michel Benkert (University of Zurich, Department of Economics, 2015)
We study the bilateral trade problem put forward by Myerson and Satterthwaite (1983) under the assumption that agents are loss-averse. We use the model developed by Koszegi and Rabin (2006, 2007) to find optimal mechanisms for the minimal subsidy, revenue maximization and welfare maximization problem. In both, welfare and revenue maximizing mechanisms, the designer induces less trade in the presence of loss-aversion. Intuitively, the designer is providing the agents with partial insurance. Moreover, the designer optimally provides the agents with full insurance in the money dimension, i.e. she offers deterministic transfers. Another implication of loss-aversion is that it increases the severity of the impossibility problem, that is, the minimal subsidy needed to induce materially efficient trade is higher. All results display robustness to the exact specification of the reference point. We also provide some general mechanism design results.
Keywords: C78; D02; D03; D82; D84; 330; Bilateral Trade; Loss-Aversion; Mechanism Design; Deterministic Transfers